2018
DOI: 10.1371/journal.pone.0203942
|View full text |Cite
|
Sign up to set email alerts
|

Hyponatremia and the risk of kidney stones: A matched case-control study in a large U.S. health system

Abstract: Kidney stones impose a large and increasing public health burden. Previous studies showed that hyponatremia is associated with an increased risk of osteoporosis and bone fractures, which are also known to be associated with kidney stones. However, the relation between hyponatremia and kidney stones is not known. To assess the relation between hyponatremia and kidney stones, we designed a matched case-control study by using the electronic health records of the MedStar Health system with more than 3.4 million un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…A recent article has reported that chronic hyponatremia (mainly due to SIADH) is associated with a higher risk of kidney stones [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent article has reported that chronic hyponatremia (mainly due to SIADH) is associated with a higher risk of kidney stones [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…X-ray powder diffraction is easy and can be done on small stone samples. It can accurately analyze the crystal components of the stone and differentiate between them [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Hyponatremia is a prevalent disorder of water homeostasis in a variety of clinical settings. Hyponatremia is associated not only with falls, fractures, osteoporosis, and kidney stones but also with a higher likelihood of morbidity and mortality, which are significant social issues (1)(2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%